Exploration of Novel Thiazole Scaffolds with Potential Therapeutic Applications - Gopi, Chandravadivelu; Dhanaraju, Magharla Dasaratha; Naga Devi, Eethakota Parimala; Supriya, Irpa; Pravallika, Gullapudi Durga (Asian Journal of Chemistry, 2026)
This study focuses on the synthesis and evaluation of the antimicrobial, anti-inflammatory and antipyretic activities of novel thiazole-based Schiff base derivatives (S1-S6). The compounds were synthesized through condensation reactions between 2-aminothiazole and several aromatic aldehydes. Structural characterization of the synthesized derivatives was carried out using FTIR, 13C NMR, 1H NMR, mass spectrometry techniques and elemental analysis. Initially, thiazole-based Schiff base derivatives therapeutic activities were assessed from AutoDock score after the successful binding with Staphylococcus aureus DNA gyrase B and cyclooxygenase 2. The synthesized derivatives were also evaluated for antimicrobial, anti-inflammatory and antipyretic activities using in vitro and in vivo methods. Compounds S6 and S1 showed the highest activity, possibly due to the thiazole nucleus linked to furan and substituted aromatic rings. The experimental findings were consistent with the in silico molecular docking results.